THE PHILOSOPHY OF COSMIZM: ETHICAL END - Перевознік, Л. М. (Proceedings of the National Aviation University Series Philosophy Cultural, 2021)
The author of the article investigates the problem of harmonization of a human being and nature through the ethical principles and norms of behavior in the natural environment.